Does darurah concept still a dispensation to takaful operators in Malaysia? - Hartini, Ab Ghani; Salman, Lambak (2015)
The Shariah compliant insurance embedded with Shariah principles emerged as the solution for the Muslims who have been avoiding conventional insurance as it is haram (unlawful) to the Muslims. The unlawful is applicable not only to conventional insurance but also to reinsurance. However, the Takaful operators in Malaysia need to depend on reTakaful operators to ensure the continuity of the Takaful operators in the long term by spreading the risk to reTakaful operators. However, lack of reTakaful operators in the market, left Takaful operators with the dilemma of having reinsure on a conventional basis in meeting the market demands, Hence, the Shariah Supervisory board, Central Bank of Malaysia has given a temporary dispensation to Takaful operators to reinsure on reTakaful conventional basis. The arrangement of Takaful operators on the conventional reinsurance is based on the principle of darurah. Recently, more licenses issued by Central Bank of Malaysia to companies to operate re-Takaful business This paper therefore intends to discuss whether “darurah” is still holds some ground in reTakaful.